Pengamalan Tarekat Alqodiriyyah Sebagai Pendidikan Tauhid di Pondok Pesantren Hidayatussalikin Pangkalpinang - Dewi, Ratna (Scientia: Jurnal Hasil Penelitian, 2023)
This study aims to find out clearly about the practice of the Alqodiriyyah congregation as a monotheistic education system. The location in this study is at the Hidayatussalikin Islamic Boarding School in Pangkalpinang.To answer these questions, this research uses qualitative descriptive research methods. The data sources used are primary data and secondary data. While the method of collecting data through observation, interviews, and documentation with data analysis, namely data reduction, data presentation and drawing conclusions. The findings of this study indicate that the values ​​of tauhid education in this pesantren consist of the elements of monotheism 'rububiyah, monotheism 'uluhiyah and monotheism 'al-Asma wa al-Shifat. While the scope of monotheism education material is: 'Ilahiyyat, Nubuwat, Ruhaniyat. Sam'iyyat. The characteristics of the pesantren are monotheism learning and congregational learning, especially the Alqodiriyyah congregation. As for the practices of the Alqodiriyyah order at the Islamic boarding school, they are the remembrance of "jahar" and the remembrance of "khafi". Meanwhile, the impact of the practice of the Al-Qodariyyah congregation on monotheism education has experienced a significant increase, namely obedience in worship, honesty, caring, gratitude and patience.